Meningkatkan Percaya Diri Pada Anak Perempuan Guna Mengatasi Pencabulan Usia Dini - Novita Purba; Fajar Utama Ritonga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Beliefs that are owned by someone that is positive and must be owned by everyone who is born from oneself without any coercion from others to admit a reality that can be accepted by others. Strong interactions from time to time foster mutual trust and high solidarity. This can be seen from the mutual trust and sense of comfort. The social relationships that have been formed move them to see and form networks and have goals. This is very influential on its implementation effectively, and to maintain each individual who is emphasized for norms and rules that have been mutually agreed upon. Self-knowledge and interests are very difficult if done by individuals alone, therefore values, norms, self-confidence, are very important. especially in today's era, there are very minimal morals, so that it can damage their identity. There are also those who have good morals for children and are in accordance with their abilities as well as interesting interests and talents so that they can develop the capability to learn and work optimally with great enthusiasm.